The Effect Of "Kim's Memory Game" On Students' Vocabulary Mastery Viewed From Students' Motivation(An Experimental Study at the Seventh Grade Students of SMP N 2 Pedan, Klaten in the Academic Year 2016/2017) - Siti Hajar, Wahyuningtyas; , Dr. Maryadi, MA (2017)
ABSTRACT The main objectives of this study are: (1) to find out whether there is any different influence on Kim's memory game and Translation toward students' vocabulary mastery of the seventh grade students of SMP N 2 Pedan, Klaten in the academic year 2016/2017. (2) to find out whether there is any different influence of of high students' motivation and low students' motivation toward students' vocabulary mastery of the seventh grade students of SMP N 2 Pedan, Klaten in the academic year 2016/2017. (3) to find out whether there is the influence of the interaction between learning technique and students' motivation toward students' vocabulary mastery of the seventh grade students of SMP N 2 Pedan, Klaten in the academic year 2016/2017. This study is experimental study. The population of the research is 331 students of seventh grade students' of SMP N 2 Pedan, Klaten in the academic year 2016/2017. The total sample were 62 students' taken from two classes, 7D and 7E were the sample. The instrument of this research is vocabulary test and questionnaire. In analyzed the data using ANOVA or multifactor analysis and Tukey test. The research findings show that: (1) using Kim's memory game is better than using translation for teaching vocabulary mastery at seventh grade students of SMP N 2 Pedan, Klaten in the academic year 2016/2017. (2) the students who have high motivation have better vocabulary mastery than the students who have low motivation at the seventh grade students of SMP N 2 Pedan, Klaten in the academic year 2016/2017. (3) there is no influence of the interaction between teaching technique and students' motivation in teaching vocabulary mastery at the seventh grade students of SMP N 2 Pedan, Klaten in the academic year 2016/2017. Keywords: Kim's memory game, Motivation, Vocabulary